Difficulties in language learning and types of errors - Saliyeva Shakhlo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
As it is known that learning and teaching a foreign language can be a difficult matter because of different pronunciation, grammar and sentence structure of languages. It is not an easy matter to avoid such mistakes and errors while learning languages. However, there are a number of ways for solving language problems in teaching. The work is devoted to errors and difficulties in language learning and solutions for this matter. In linguistics, according to J.Richard et al an error is the use of a word, speech act or grammatical items in such a way it seems imperfect and significant of an incomplete learning. It is considered by Norrish as a systematic deviation that happens when a learner has not learnt something and consistently gets it wrong. However, the attempts made to put the error into context have always gone hand in hand with either language learning and second language acquisition processes.